Novel InAs HEMT Architectures for Terahertz Applications - N. Mohankumar, M. Sunil, B. G. Raghunath, Katakam Jyothiprakash, Girish Shankar Mishra, M. Arun Kumar, R. Poornachandran, D. Godwinraj (International Journal of Advanced Science and Technology, 2020)
This article reports a systemic theoretical study of the microwave noise performance of the InAs high electron mobility transistor (HEMT) based on a double quantum well dual gate. For this analysis, the double quantum well HEMT shows a prominent analog / RF small signal and current performance. The data on the 30 nm gate length unit give a 0.126V threshold voltage (Vt) enhancement mode of operations, 3.67S/µm high transconductance with 645GHz cut-off frequency (ft) and 1.2THz maximum frequency of oscillation (fmax) in Vds = 0.5V. This study shows that InAs HEMT is well suited for higher and low noise requirements with a dual quantum well structure.